Application of Support Vector Machines to the Modelling of Inflation - Marcek, Dusan; Marcek, Milan (Communications - Scientific letters of the University of Zilina, 2005)
In Support Vector Machines (SVM’s), a non-linear model is estimated based on solving a Quadratic Programming (QP) problem. Based on work [1] we investigate the quantifying of econometric structural model parameters of inflation in Slovak economics. The theory of classical Phillips curve [8] is used to specify a structural model of inflation. We provide the fit of the models based on econometric approach for the inflation over the period 1993-2003 in the Slovak Republic, and use them as a tool to compare their approximation ability with those obtained using SVM’s method. Some methodological contributions are made for SVM implementations to the causal economic modelling.